RDB (Reinforcement of Dignified Behavior): A Strategy to Keep Talented Employees Stay Longer - Sugiyono; Suharnomo (International Journal of Psychosocial Rehabilitation, 2020)
Recognizing the important role of talented personnel, each organization seeks to bind and detain them through a variety of strategies, such as the provision of compensation packages or more competitive incentives. However, employees who have held high positions have other considerations for staying or leaving the company. The purpose of this study was to analyze the effect of Reinforcement of Dignified Behavior on talent retention. The population was 1320 consisted of 264 principals and 1056 Vice-Principals working under the administration of Semarang residency, among which 400 respondents were chosen and sampled to be 250 samples. Data were collected through questionnaires shared directly in a meeting and google quest. The data collected were analyzed using structural equation model (SEM) with AMOS21 software. The result showed that Reinforcement dignified behavior had a significant positive effect on talent retention.